PROTECTION OF CHILDREN FROM DOMESTIC VIOLENCE: A COMPARATIVE STUDY OF ISLAMIC LAW AND POSITIVE LAW IN INDONESIA - Eva Fadhilah; Öğretim Üyesi Büşra Nur DURAN; Pitrotussaadah (Universitas Islam Indonesia, 2025)
Purpose - This study aims to examine and compare the principles of child protection in Islamic and positive law in Indonesia, focusing on the handling and prevention of violence against children within the family. The significance of this research lies in the increasing number of child abuse cases, particularly within the household, which indicates a gap between existing legal norms and social realities. Method - This study used a qualitative approach with a normative juridical method. Data were collected through a literature review, including primary sources (the Qur’an, Sunnah and Statutory regulations) and secondary sources (classical books and scholarly journals). Findings - Islamic law firmly rejects all forms of violence against children through principles contained in the texts and the concept of Maqāṣid al-Usrah, which provides guidance for child protection from conception to adulthood. Positive law regulates child protection through Law No. 35 of 2014, which covers investigations, court proceedings, victim rehabilitation, and prevention through education and child protection institutions. The implementation of both legal systems is hindered by differing interpretations and cultural influences on the law. Research Contribution/Limitations-This study provides a comparative overview of the relevance of child protection principles in Indonesia, but is limited to literature-based research. Originality/Value-This research enriches child protection studies by integrating Islamic and positive legal perspectives as academic and practical references for child protection.